The use of Pentacam for keratoconus diagnosis and progress evaluation - Kopacz, Dorota; Maciejewicz, Piotr; Kęcik, Dariusz (Klinika Oczna / Acta Ophthalmologica Polonica, 2011)
The authors present possibilities of Pentacam examination for keratoconus diagnosis and progress evalutaion. They describe meaning of data comming from Pentacam 3D model measurements; indexes for corneal surface disturbances, analysis of anterior and posterior corneal surface, sense of connection data from keratometric and pachymetric measurements for keratoconus detection.